Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Perbankan Pada PT. Bank Muamalat Di Salatiga - setyaningrum, dewi probowati (2016)
This study aims to determine the effect of financial ratios of the financial performance of banks. This study uses primary and secondary data. The primary data obtained through interviews waancara or directly with the PT. Bank Muamalat Salatiga. Samples taken in this research is financial statement of the balance sheet and income statement over the period 2012 - 2014, with the sampling technique used purposive sampling method. Based on the results of research, data analysis, and discussion in the previous chapter, it can be concluded that the hypothesis. There is the influence of the financial ratios of financial performance banking on PT. Bank Muamalat in Salatiga is received, because of each variable RORA, DER, NPM and ROI have a significant impact on financial performance. So with this financial ratio analysis can know their financial performance at PT. Bank Muamalat in Salatiga in 2012 until 2014.